Correction: Transport mechanisms in a puckered graphene-on-lattice. Issue 14 (26th March 2019) - Xu, T.; Díaz Álvarez, A.; Wei, W.; Eschimese, D.; Brillard, C.; Eliet, S.; Lancry, O.; Galopin, E.; Vaurette, F.; Berthe, M.; Desremes, D.; Wei, B.; et al.
Abstract : Correction for 'Transport mechanisms in a puckered graphene-on-lattice' by T. Xu et al., Nanoscale, 2018, 10, 7519–7525.